Regulación del medio ambiente y competitividad - Panayotou, Theodore (1999)
Environmental regulations can affect productivity in various ways: diverting inputs to the so-called non-productive uses or originating less efficient production processes. Adequate environmental regulations should generate benefits that exceed their costs although not all benefits can be translated into the increase of the product.